2016
DOI: 10.1002/jctb.5084
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of cultivation conditions for combined nutrient removal and CO2fixation in a batch photobioreactor

Abstract: BACKGROUND: The application of Chlorella vulgaris for simultaneous CO 2 biofixation and nutrient removal has been optimised using response surface methodology (RSM) based on Box Behnken design (BBD). Experimental conditions employed comprised CO 2 concentrations (C c,g ) of 0.03-22% CO 2 , irradiation intensities (I) of 100-400 E, temperatures of 20-30 ∘ C and nutrient concentrations of 0-56 and 0-19 mg L −1 nitrogen and phosphorus, respectively, the response parameters being specific growth rate , CO 2 uptake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…Recorded growth rates were higher than those of Kim et al [14], who reported X and C d values of 0.78 g L -1 and 17.5× 10 6 cells mL -1 respectively using LED lighting providing a wavelength band of 400-460 nm and an I of 100 µE m -2 s -1 . A 78% reduction in incident I to approximately 55 µE m -2 s -1 was recorded for CT B , decreasing the level of photosynthesis active radiation (PAR) and thus photosynthesis activity accordingly [24]. At lower I up to 80% of the theoretical maximum photosynthesis efficiency (PE) can be achieved [4][5][6][7], although a reduced I value results in a proportionally lower biomass production.…”
Section: Influence Of I and λ Max On Cv Growthmentioning
confidence: 97%
See 1 more Smart Citation
“…Recorded growth rates were higher than those of Kim et al [14], who reported X and C d values of 0.78 g L -1 and 17.5× 10 6 cells mL -1 respectively using LED lighting providing a wavelength band of 400-460 nm and an I of 100 µE m -2 s -1 . A 78% reduction in incident I to approximately 55 µE m -2 s -1 was recorded for CT B , decreasing the level of photosynthesis active radiation (PAR) and thus photosynthesis activity accordingly [24]. At lower I up to 80% of the theoretical maximum photosynthesis efficiency (PE) can be achieved [4][5][6][7], although a reduced I value results in a proportionally lower biomass production.…”
Section: Influence Of I and λ Max On Cv Growthmentioning
confidence: 97%
“…CT w provided a light wavelength range of 750-350 nm, with a peak of 413 nm, and reduced the control I (U) of 250 µE m -2 s -1 by about 50%. Non-photochemical quenching (NPQ) is known to arise if the rate of photo-inhibition exceeds the rate of repair, resulting in a large proportion of the captured light being dissipated at high I [24]. The lower X and µ values obtained for U suggest that growth is reduced at longer random wavelengths [10].…”
Section: Influence Of I and λ Max On Cv Growthmentioning
confidence: 99%
“…Light intensities providing a reasonable specific growth rate (μ) and biomass productivity (P bio ) reported for Chlorella vulgaris (C.V), the most commonly studied strain, varied widely at 40-1240 μE.m −2 .s −1 (Abou -Shanab et al, 2013;Abreu et al, 2012;AlMomani and Örmeci, 2016;Lam and Lee, 2013;Li et al, 2003;Marbelia et al, 2014;Ruiz-Martinez et al, 2012;Znad et al, 2018a). According to the C.V literature at an optimum light intensity of 100 μE.m -2 .s -1 and 5% C c,g , the associated maximum μ, and P bio values are around 1.17 d -1 and 0.74 g.L -1 .d -1 respectively at a temperature of 24°C for a batch cultivation process (Abreu et al, 2012;Al Ketife et al, 2017;Li et al, 2013). This compares to a reasonable growth rate at a narrower range of 68-400 μE.m −2 .s −1 for SP.PL (Ho et al, 2018;Kumari et al, 2014;Liu et al, 2018;Singh et al, 2016;Xue et al, 2011;Yuan et al, 2011;Zhou et al, 2017b).…”
Section: 1mentioning
confidence: 99%
“…There has been increasing focus on the use of microalgal culture technology (MCT) for both bio-fixation of CO 2 from flue gases (Adamczyk et al, 2016;Al Ketife et al, 2017;Almomani et al, 2017;Razzak et al, 2013;Toledo-Cervantes et al, 2018;Zhou et al, 2017a;Zhou et al, 2017b) and removal of nutrients from wastewater (AlMomani and Örmeci, 2016;Arbib et al, 2017;Gao et al, 2018;Sutherland et al, 2014;Sutherland et al, 2015;Zhou et al, 2017a;Znad et al, 2018a), with the technical and cost implications of the combined process also recently considered (Judd et al, 2017;Kasprzyk and Gajewska, 2019). The use of biology for carbon capture and direct generation of useful products, predominantly biofuel (Bai and Acharya, 2017;de Godos et al, 2014;Fernández et al, 2012;Kassim and Meng, 2017;Singh et al, 2016;Zhang et al, 2011), obviates the energy-intensive solvent regeneration step of the conventional absorption process for carbon capture (Hammond and Spargo, 2014;Wang et al, 2017;Wilberforce et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation